2012
DOI: 10.1111/j.1750-2659.2012.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of viral infections in children with community‐acquired pneumonia: results of a study of 17 respiratory viruses

Abstract: Please cite this paper as: Esposito et al. (2012) Impact of viral infections in children with community‐acquired pneumonia: results of a study of 17 respiratory viruses. Influenza and Other Respiratory Viruses DOI: 10.1111/j.1750‐2659.2012.00340.x. Background  Little is known about the prevalence of viral infections in children with community‐acquired pneumonia (CAP). Objectives  To describe the clinical and virological data collected from children with radiographically confirmed CAP in whom 17 respiratory vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
114
5
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(141 citation statements)
references
References 35 publications
10
114
5
12
Order By: Relevance
“…The influenza virus is the most frequent viral pathogen detected in adult patients with CAP as our study demonstrates, which is inconsistent with the fact that the respiratory syncytial virus is the leading viral pathogen in pediatric patients with CAP [39,40,41,42]. Influenza vaccination has been previously proven to be efficient in preventing influenza viral infections especially during a pandemic influenza period [43].…”
Section: Discussioncontrasting
confidence: 43%
“…The influenza virus is the most frequent viral pathogen detected in adult patients with CAP as our study demonstrates, which is inconsistent with the fact that the respiratory syncytial virus is the leading viral pathogen in pediatric patients with CAP [39,40,41,42]. Influenza vaccination has been previously proven to be efficient in preventing influenza viral infections especially during a pandemic influenza period [43].…”
Section: Discussioncontrasting
confidence: 43%
“…France, Spain, and Australia); information on NPEV circulation in Italy derived exclusively from occasional studies in particular population, especially in children affected by severe pathological conditions. [37][38][39][40][41][42] In conclusion, AFPS proved to be successful especially after the PHEIC declaration and ES revealed a wide NPEVs circulation, mainly supported by echovirus type 11, 6 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, multiple infections have been reported to induce a less favorable prognosis [8]. In contrast, Esposito, et al (2013) reported that the difference in LOS between single (6.9 days) and multiple infections (7.1 days) was not significant. Other studies have reported no difference in clinical symptoms, prognosis, or intensive care unit admission rates between single and multiple infections [21][22][23], with some reporting less severe disease in patients with multiple respiratory virus infections [24,25].…”
Section: Discussionmentioning
confidence: 66%